25th AIAA Aerodynamic Measurement Technology and Ground Testing Conference 2006
DOI: 10.2514/6.2006-2955
|View full text |Cite
|
Sign up to set email alerts
|

Free-Jet Testing of a REST Scramjet at Off-Design Conditions

Abstract: Scramjet flowpaths employing elliptical combustors have the potential to improve structural efficiency and performance relative to those using planar geometries. NASA Langley has developed a scramjet flowpath integrated into a lifting body vehicle, while transitioning from a rectangular capture area to both an elliptical throat and combustor. This Rectangular-to-Elliptical Shape Transition (REST) scramjet, has a design point of Mach 7.1, and is intended to operate with fixed-geometry between Mach 4.5 and 8.0. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Stalker et al (2005) provide an detailed summary covering the period up to 2005. Furthermore, results from the HyShot II flight experiment were found to match results from experiments conducted in the t4 Stalker Tube (Smart, 2006), providing further evidence of the validity and usefulness of shock tunnel testing for the development of scramjet engines.…”
Section: Forebody Flow Conditionssupporting
confidence: 59%
See 2 more Smart Citations
“…Stalker et al (2005) provide an detailed summary covering the period up to 2005. Furthermore, results from the HyShot II flight experiment were found to match results from experiments conducted in the t4 Stalker Tube (Smart, 2006), providing further evidence of the validity and usefulness of shock tunnel testing for the development of scramjet engines.…”
Section: Forebody Flow Conditionssupporting
confidence: 59%
“…A six-component force balance was also used but facility-model interactions in the larc chstf prevented net force data from being measured; only the force increment due to combustion could be quantified. Furthermore, Smart and Ruf (2006) did not provide any details concerning the geometry of the isolator, combustor, nozzle or fuel injection station and all plots were shown in the paper without axis limits.…”
Section: Rest Engine Design and Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The engine was found to be self-starting, even under mechanically induced engine unstart conditions, and remained started with back-pressure ratios as high as 5.7. Further testing with the injection and combustion of hydrogen fuel under Mach 5.3 flight conditions showed that the engine maintained robust combustion for fuel equivalence ratios between 0.5 and 1.5 (Smart and Ruf, 2006). The engine remained self-started under a variety of adverse conditions, though at the lower range of Mach numbers (i.e.…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…This fixed-geometry mixed-compression configuration transitions smoothly from a quasirectangular capture shape to an elliptical throat. In combination with a divergent elliptical combustion chamber, REST inlets have been shown to produce a useful flowpath for hypersonic applications [20]. The current configuration is an exploratory Mach 8.1 design-point flowpath which has been explicitly adapted to be used in conjunction with inlet injection and radical farming.…”
mentioning
confidence: 99%